STAGES OF SPEECH DEVELOPMENT IN EARLY CHILDREN - Phd Maxmudova Madinaxon Sobirxonovna; Sidiqova Baxtigul Kabirjon qizi (Bright Mind Publishing, 2025)
This article systematically covers the stages of speech development in early childhood. The article describes in detail the process of gradual speech formation in the period from 0 to 3 years, the stages of growth of infants from the moment of sound production to the first meaningful words.
Keywords: Speech, development, early childhood, child, baby, sound, word, communication, language, speech stages, speech formation.